1990
DOI: 10.1128/iai.58.3.711-718.1990
|View full text |Cite
|
Sign up to set email alerts
|

Effective vaccination of mice against leprosy bacilli with subunits of Mycobacterium leprae

Abstract: Model vaccines against leprosy bacilli have consisted of nonvirulent, live, attenuated Mycobacterium bovis BCG and irradiated, heat-killed, or autoclaved intact M. leprae. We report that immunization with various cell wall fractions of M. leprae, progressively depleted of lipids, carbohydrates, and soluble proteins, as well as a partially purified protein(s) derived from a pellet fraction of sonicated M. keprae, conferred significant protection against subsequent infection with live leprosy bacilli. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…Patients wilh active tuberculosis showed intermediate responses to cell wall proteins proportional to their responses to the whole leprosy bacillus. We also confirm that the cell wall proteins dieting these responses were able to stimulate protective immunity in mice against M. leprae foot-pad infection [13].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Patients wilh active tuberculosis showed intermediate responses to cell wall proteins proportional to their responses to the whole leprosy bacillus. We also confirm that the cell wall proteins dieting these responses were able to stimulate protective immunity in mice against M. leprae foot-pad infection [13].…”
Section: Introductionsupporting
confidence: 75%
“…Protection against M. leprae infection can be induced by prior vaccination with live or dead M. leprae, BCG [24] or M. habana [25]. Recently, immunization with cell wall preparations of M. leprae, including extractable cell wail proteins, resulted in significant inhibition of the growth of M. leprae and corresponding T cell reactivity [13]. Although the degree of protection induced by immunization with the CWP in the present study was variable (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…In separate studies this protein was also found responsible for generation of high titres of specific antibodies in leprosy patients, having implications for diagnosis and patient care [33,42], However, an attempt to vaccinate mice with 35 kD protein against footpad challenge with Myco. leprae did not succeed [45], despite earlier encouraging results [46]. The 22 kD Myco.…”
Section: Discussionmentioning
confidence: 93%
“…Though T lymphocytes play a major role in protection against facultative intracellular bacteria, antigens relevant to the humoral immune response have been studied more extensively than T-cell antigens because antigens recognized by antibodies are more technically amenable to study (40). To identify antigens recognized by T lymphocytes, complex protein preparations from intracellular bacteria have been used to investigate the cellular immune response (12,18,37). However, isolation of individual stimulatory components in complex mixtures is still difficult.…”
mentioning
confidence: 99%